Complementarities and Cumulative Processes in Models of Monopolistic Competition - Matsuyama, Kiminori (Journal of Economic Literature, 1995)
Monopolistic competition models have frequently been applied in macroeconomics, growth and development, and international and interregional economics. The three features of monopolistic competition, the monopoly power of producers, the lack of strategic interaction, and endogenous product variety, make it a useful framework to examine the aggregate implications of imperfect competition, increasing returns and incomplete markets. This papers presents a highly selective review in this area, with special emphasis on complementarity and its role in generating multiplier processes, business cycles, clustering, underdevelopment traps, regional disparities, and sustainable growth, or more generally, what Myrdal (1957) called the principle of circular and cumulative causation. (This abstract was borrowed from another version of this item.)